EVALUATION OF THE FATIGUE BEHAVIOR OF STONE MASTIC ASPHALT MODIFIED BY DOMESTIC WASTE BIO-ASPHALT - Abd Tayh, Sady; Muniandy, Ratnasamy; Hassim, Salihudin; Mohd Jakarni, Fauzan (Journal of Engineering and Sustainable Development, 2018)
This paper presents the results of a laboratory study based, upon evaluating the fatigue characteristics of Stone Matrix Asphalt (SMA) Mixtures using different percent of bio-oil produced from pyrolysis process of house hold waste. The indirect tensile fatigue (ITFT) test was used to study fatigue behavior. The fatigue tests were performed at three temperatures (15, 20, and 25°C) using one asphalt binder, 80/100 penetration asphalt. The outcomes demonstrated that the addition of DWBO has slightly lowered the resilient modulus, and reduced the fatigue performance of the SMA Mixtures. For the effect of the temperature on fatigue life of 80/100 bio-binders, it is reasonable to use DWBO in asphalt mixture as an additive in cold to moderate temperature regions. The study shows that the DWBO can be used with petroleum binders in the pavement industry with a percent not exceeding 3% by weight of the base binder.